That divine order: music and the visual arts from antiquity to the eighteenth century - Vergo, Peter (London [etc.] : Phaidon Press, 2005)
Summary :his exploration of the relationship between music and the visual arts examines how it was conceived at various times by practising artists and musicians, and also by critics and theorists of art. his scholarly, yet jargon-free, exploration of the relationship between music and the visual arts examines how that relationship was conceived at various times by practising artists and musicians, by critics and theorists of art Review: 'This is a fine book for students of art and music, which has been thoroughly researched and cogently written. It is also liberally illustrated with monochrome figures and a number of coulour plates.' (Musical Opinions)
Naslovi poglavlja : Introduction -- The Cry of the Phoenix -- Spherical Music -- Gothic Architecture and Polyphony -- Divine Harmonies -- Mode and Mood -- Melodies for the Eye -- Epilogue: Colour-music -- Notes -- Bibliography -- Index.
Bibliografija - Kazala
Keywords: metodika nastave -- muzika, muzički motivi u pov. umjetnosti -- vizualna umjetnost -- arhitektura i glazba -- teorija glazbe -- muzikologija